Epilepsy and cataplexy in Angelman syndrome. Genotype-phenotype correlations. (September 2016) - Granild Bie Mertz, Line; Christensen, Rikke; Vogel, Ida; Hertz, Jens Michael; Østergaard, John R.
Highlights: All children with AS due to a deletion developed epilepsy. Epilepsy onset occurred significantly earlier among children with deletion compared to children with UBE3A mutation or pUPD. Laughter-induced postural muscle tone loss occurred only among deletion cases. We found no differences in severity of epilepsy between children with Class I or Class II deletions. The drugs most frequently prescribed were benzodiazepines in monotherapy, or a combination of benzodiazepines and valproic acid. Abstract: Background: Angelman syndrome (AS) is a neurogenetic disorder characterized by intellectual disability, epilepsy, and low threshold for laughter. Aims: We investigated the occurrence and severity of epilepsy and laughter-induced loss of postural muscle tone determined by the different genetic subtypes. Methods: This study included 39 children with AS. Deletion breakpoints were determined by high resolution CGH microarray (1 × 1 M Agilent). Clinical data were based on a parent interview and medical record review. Results: All patients with AS based on a deletion had epilepsy. Epilepsy was present in 3/4 children with UBE3A mutation, and 4/5 with pUPD. Onset of epilepsy occurred earlier in deletion cases compared to pUPD or UBE3A mutations cases. Laughter-induced postural muscle tone loss occurred only among deletion cases. We found no differences in severity of epilepsy between children with a larger Class I or a smaller Class II deletions, or between the total group with a deletion compared to children with pUPD or a UBE3A mutation. The drugs most frequently prescribed were benzodiazepines in monotherapy, or a combination of benzodiazepines and valproic acid. Conclusion: Epilepsy is very common in patients with AS, especially in patients with a deletion. Postural muscle tone loss and collapsing during outbursts of laughter were seen in patients with a deletion only.